2020
DOI: 10.3354/esr01007
|View full text |Cite
|
Sign up to set email alerts
|

Using small drones to photo-identify Antillean manatees: a novel method for monitoring an endangered marine mammal in the Caribbean Sea

Abstract: Population assessments and species monitoring for many endangered marine megafauna are limited by the challenges of identifying and tracking individuals that live underwater in remote and sometimes inaccessible areas. Manatees can acquire scars from watercraft injury and other incidences that can be used to identify individuals. Here we describe a novel method for photo-identification of Antillean manatees Trichechus manatus manatus using aerial imagery captured during flights with a small multirotor drone. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…Regarding imagery for photo-ID purposes, the representative features and scars can be distorted or masked due to ripples, light diffusion on water, and turbidity [117]. It is also challenging to obtain manatee images depicting the whole body in straight position and near surface, most suitable for photogrammetry purposes.…”
Section: Methodological Difficultiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding imagery for photo-ID purposes, the representative features and scars can be distorted or masked due to ripples, light diffusion on water, and turbidity [117]. It is also challenging to obtain manatee images depicting the whole body in straight position and near surface, most suitable for photogrammetry purposes.…”
Section: Methodological Difficultiesmentioning
confidence: 99%
“…Both multirotor and fixed-wing drones can be used for the purpose of detecting sirenians (e.g., [15,117]). On the other hand, multirotor drones can maintain stationary flight, allowing the capture of high-quality images and videos of surfacing marine mammals [114], which can be useful for studies based on photogrammetry and photo-identification.…”
Section: Drone Selection For Sirenian Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…UAVs have become waterproof and more affordable, with longer battery life, larger ranges of travel, and reduced noise production (Christiansen, Rojano‐Doñate, Madsen, & Bejder, 2016; Fiori, Doshi, Martinez, Orams, & Bollars‐Breen, 2017). While applications of UAVs to cetacean research have typically centered on abundance estimates, photogrammetry, and photo‐identification (Durban et al, 2016; Fiori et al, 2017; Koski et al, 2015; Landeo‐Yauri, Ramos, Niño‐Torres, Castelblanco‐Martinez, & Searle, 2019), some recent research efforts have assessed behavioral patterns (Fiori, Martinez, Bader, Orams, & Bollard‐Breen, 2019; Nielsen, Sprogis, Bejder, Madsen, & Christiansen, 2019; Torres, Nieukirk, Lemos, & Chandlerm 2018; Weir et al, 2018). Our objective was to assess the behavioral patterns of dusky dolphins in mating groups collected from UAV footage.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings illustrate the power of small aerial drones to track and document the fine‐scale behavior of dolphins (Orbach et al, 2020; Ramos et al, 2018a; Weir et al, 2018). Similar to other marine mammals (e.g., Hartman, van der Harst, & Vilela, 2020; Landeo‐Yauri et al, 2020), individual rough‐toothed dolphins can be identified by their scarring and skin pigmentation patterns. Future studies should focus on understanding the long‐term social structure of this species (stability of associations), in particular as it relates to cooperative foraging (e.g., prey sharing and group hunting).…”
Section: Figurementioning
confidence: 94%